Pendidikan Karakter melalui Pendidikan Pancasila: Membangun Generasi Unggul dengan Nilai-Nilai Kebangsaan - Furnamasari, Yayang Furi; Adriawan, Aura Nazwa Ar'zahra; Fitriani, Feni; Aditya, Ferdino Arief; Eliza, Hanum; Fuadah, Intan Samrotul; Amalia, Larissa Suci; Daud, Muhammad Rafi Bahiruddin; Shidiqqa, Queeny Qolbi Ash (Indo-MathEdu Intellectuals Journal, 2024)
Character education is an important aspect in building the quality of human resources that can compete and have strong good values. With the need for a superior generation who have a strong national and moral identity, Pancasila Education is considered as a relevant foundation to form a character that is in accordance with national values. This study aims to explore the potential of Pancasila education in forming young people who have integrity, social responsibility, and love for the nation and state. The research method used in this study is a qualitative research method using literature study techniques. The main source of research data comes from research articles published through Google Scholar. Data analysis is carried out qualitatively with stages of data reduction, data presentation, and conclusions. The results of data analysis show that character education should be the key that has an important role in building a superior generation of the nation in accordance with the values of Pancasila. With the instillation of Pancasila values in the nation's generation, the functions and roles of Pancasila will still be carried out as they should.